Penegakan Hukum Atas Penyalahgunaan Letter of Credit Sebagai Alat Pembayaran dalam Transaksi Ekspor-Impor - Pelupessy, Eddy; Pelupessy, Berd Elkiopas; Khairazi, Rifqon (Penerbit Yayasan Daarul Huda Kruengmane, 2025)
This study was conducted with the aim of analyzing, explaining, and understanding the operational risks of banks on the issuance of L/C, identifying the development of crime rates through L/C and law enforcement on the misuse of L/C as a means of payment in export-import transactions. The type of research used is normative juridical, namely to examine legal concepts related to law enforcement on the misuse of letters of credit as a means of payment in export-import transactions. The results of this study reveal that the presence of fictitious documents as a means of disbursing L/C clearly contains evil motives coloring bank break-ins, as a bank that is involved in the international trade area (International track Jurvice), operational risks have certainly been calculated in advance. Risk Management should understand the potential risks. The risks that can occur in connection with the involvement of banks as guarantors and mediators between sellers and buyers from different countries. Of course it is also riskier to provide dual facilities to one customer as an importer and exporter customer at the same time. Therefore, law enforcement on the misuse of letters of credit is the application of the principle of knowing the customer which is the embryo of the principle of maximum prudence in order to minimize crime in the banking sector.